Chiral phosphoramide-catalyzed, enantioselective, directed cross-aldol reactions of aldehydes - Denmark, Scott E. (National Academy of Sciences, 2004)
Catalytic, enantioselective, directed cross-aldol reactions of aldehydes are described. The addition of isobutyraldehyde trichlorosilyl enolate 2 to various aldehydes in the presence of 10 mol % bisphosphoramide 4 provides aldol products in high yields with moderate to good enantioselectivities. The reaction works well with a wide range of aromatic, olefinic, and aliphatic aldehydes. Enantioselectivities are highly dependent on the electronic nature of the aldehyde substituent. Hammett studies reveal that enantioselectivity increases as aldehydes become either more electron rich or more electron poor.